Análise discursiva de documentos oficiais sobre o sujeito surdo - Carvalho, Lílian Pereira de (2012)
According to the census that was made in Brazil in 2000, around 5.800.000 people have some degree of hearing loss or deafness. Among them, the numbers of deaf people who don t hear anything, classified as incapable of hearing and that use the sign language to communicate was 176.067 people. Our research aims to analyze the images discursively that the official documents compose about this important part of society that can not hear. To do this, we will consider the lexical choices made, through words or statements, when those document refer to the deaf. It was mobilized the notion of Imaginary Formation, which will be used to analyze the build images from the self image and the deaf people, subject of the discourse. We still propose to analyze these documents as genre of discourse, as it was such proposed by Mikail Bakhtin (1997), because we believe that if we ignore the peculiarities of the genre that we will be led to formalism and abstraction, to disregard the historicity of the study and the relation between language and life. From this notion, we will also discuss the scenographies permeating these documents, in order to understand the tone of the discourse. To compose the corpus, some laws or decrees were chosen dealing with several issues about deaf cause such as: the sign language, their accessibility to media, theaters, public institutions, education and health, among others. These documents produced by government departments have a normative nature that aims to regulate specific actions for these subjects, especially about the guarantee of their rights. From this perspective, we will take as theoretical and methodological focus the Discourse Analysis of French orientation and the Dialogical Analysis of Discourse, through Michel Pêcheux, Dominique Maingueneau and Mikail Bakhtin studies.